Alles Schicksal?: der Himmel als astrologische Auskunftei imLuthertum der Frühen Neuzeit = Sudʹba vo vsem? : Nebo kak astrologičeskij spravočnik v ljuteranstve rannego Novogo vremeni - Sparn, Walter (Religija, cerkov', obščestvo, 2015)
The article “All is Fortune? The sky as an astrology agency in the early modern time lutheranism” deals with attitude to astrology as part of the Lutheran intellectual culture of the 16-17th centuries. The author marks outtwo distinctive approaches to astrology that were, on the one hand, the interpretation of the planets positionas the epitome of human lives, and, on the other hand, as sign of the future events. The last implies humanactions with aim of correction and perfection of the picture presented in the sky. Luther himself didn’tengaged in astrology, but it fat perfectly his eschatological consciousness. Among other reformers and Lutheran priests (Michael Stiefel, Philipp Melanchthon, Abdias Trew, etc.) astrology was considered asnecessary and honorable knowledge. Here the Melanchthon’s support of astrology in the treatise “Oratiode dignitate astrologia” 1535 was an important argument and is analyzed in detail by the author. Despite theoverall empirical character of the 16–17th centuries science within astrology was widely condemned, there had been made several attempts to reform the area. In conclusion, the author analyses astrology in the context of general Christian eschatology.